Pelatihan Bisnis Model Canvas - Nurul Hikmah; Agus Supandi; Mailizar; Retno Nengsih (CV. Multi Kreasi Media, 2023)
The development of creative ideas in small forms is growing very rapidly in the current era of technological globalization. The development of technology-based MSMEs is growing rapidly. The emergence of hundreds of start-up companies currently requires young entrepreneurs to rack their brains in competing with other competitors. A good innovation management pattern is the key to success in starting a business. Preparing knowledgeable young entrepreneurs is very important nowadays. We are required not only to be ready to work but also expected to be able to create jobs, namely to become entrepreneurs. Currently, business development in Indonesia is experiencing a very rapid increase, this can be seen from the large number of developments in small and large businesses from online and offline businesses. A business model is very important for companies because several advantages can be seen, namely: first, having a business model can help companies or business actors to get information about how, where and when the product functions well. second, designing a good business model can weaken competitors. These advantages can help companies gain competitiveness in the market. The concept of the business model canvas (BMC) is a way to describe, visualize, assess and change business models. With this business model canvas training, it is hoped that teaching staff will have sufficient knowledge in analyzing business situations and innovation management in the future.